Organizational teaching and learning – a (re)view from educational science. Issue 5 (11th July 2016) - Lahn, Leif Christian
Abstract : Purpose: The purpose of this paper is to critically examine the dominance of the participation metaphor for learning in the literature on learning organizations and to propose a working model of the teaching organization with conceptual input from educational science and the sociology of professions. Design/methodology/approach: The paper combines theoretical critique and a selective review of literature that is relevant to the discussion of the concept "teaching organization". Findings: Concepts referring to teaching as a systemic attribute of learning organizations are not made explicit in texts on organizational learning and knowing. Key concepts from educational science are almost completely absent from this literature. Originality/value: The paper describes elements from educational science and the sociology of professions and proposes to integrate them in a model of a teaching organization that could serve as a theoretical platform for further empirical studies.